AB0437 Adalimumab therapy results in sustained response in rheumatoid arthritis patients over 5 years: the german noninterventional agil study. (12th June 2018) - Behrens, F.; Schmalzing, M.; Koehm, M.; Schwaneck, E.C.; Greger, G.; Mosch, T.; Burkhardt, H.; Tony, H.-P.
Abstract : Background: Observational studies provide important insights into therapeutic response during daily clinical practice, including data on the effects of long-term treatment. Objectives: To evaluate treatment responses in rheumatoid arthritis (RA) patients during 5 years of adalimumab (ADA) therapy. Methods: We analysed data from a large German multicenter observational study of patients with active RA who initiated ADA therapy during routine clinical care (the AGIL study). Outcomes of interest included Disease Activity Score-28 joints (DAS28), DAS28 therapeutic response as assessed by the statistical critical difference (dcrit, ), 1 Health Assessment Questionnaire-Disability Index (HAQ-DI), and patient-reported global health and pain. Results: A total of 4283 patients had data available for analysis at baseline. The mean age was 55.2 years, 74% of patients were female, the mean disease duration was 9.3 years, and 26% had received previous treatment with one or more biologic drugs. At month 60, 726 patients (17%) of patients remained in the study. During the 5 year study, 41.3% of patients were lost to follow-up, 22.3% discontinued due to lack of effectiveness (about half within the first 6 months), and 4.0% discontinued due to adverse events. Mean values in patients treated with ADA showed a rapid response to treatment by both objective and patient-reported measures. Responses were maintained over 5 years in patients remaining on therapy (table 1). ADA was well tolerated and no unexpected safety signals were observed. Conclusions: The AGIL study is one of the largest observational cohorts to provide long-term data on ADA therapy. Both objective and subjective measures support the effectiveness and safety of ADA in patients with RA during 5 years of therapy. Approximately 43% of patients experienced a therapeutic response to treatment at 6 months as assessed by statistical methods (DAS28-dcrit), 1 and this level of response increased to 60% at 5 years in patients remaining on therapy. About one-third of patients recovered full functional ability (HAQ-DI remission) at the 6 month and subsequent visits. Our data indicate that ADA is an effective and safe long-term therapy in RA patients who continue on treatment. Reference: [1] Behrens F, et al. Arthritis Care Res. 2013;65:1608–16. Acknowledgements: This study was sponsored by AbbVie Deutschland GmbH and Co KG. AbbVie contributed to the study design, data analysis, and in the writing, revision, and approval of the abstract. Sharon L. Cross, Ph.D. provided medical writing services on behalf of CIRI, Frankfurt am Main, Germany, under contract with AbbVie for medical writing services and Holger Gnann, GKM Gesellschaft für Therapieforschung, Munich, Germany, provided statistical analyses as a paid consultant. Disclosure of Interest: F. Behrens Grant/research support from: AbbVie Deutschland GmbH and Co KG, Consultant for: AbbVie Deutschland GmbH and Co KG, Speakers bureau: AbbVie Deutschland GmbH and Co KG, M. Schmalzing Grant/research support from: AbbVie Deutschland GmbH and Co KG, Consultant for: AbbVie Deutschland GmbH and Co KG, M. Koehm Grant/research support from: AbbVie Deutschland GmbH and Co KG, Consultant for: AbbVie Deutschland GmbH and Co KG, E. Schwaneck Grant/research support from: AbbVie Deutschland GmbH and Co KG, Consultant for: AbbVie Deutschland GmbH and Co KG, G. Greger Employee of: AbbVie Deutschland GmbH and Co KG, T. Mosch Employee of: AbbVie Deutschland GmbH and Co KG, H. Burkhardt: None declared, H.-P. Tony Grant/research support from: AbbVie Deutschland GmbH and Co KG, Consultant for: AbbVie Deutschland GmbH and Co KG